Study of Arbuscular Mycorrhizal Fungi status at Rehabilitation Post-Nickel Mining Area (Case study at PT INCO Tbk. Sorowako, South Sulawesi) - Yadi Setiadi; Arif Setiawan (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
PT INCO Tbk. is one of the biggest nickel mining company in the Asia-Pasific region and has been operated commercially in Indonesia since 1978. It is located at Sorowako, South Sulawesi Indonesia with the area up to 218.000 hectares. The mining operation process is surface mining. It eliminated the existing vegetation, and it will lead to soil erosion, loss of biodiversity, damage of wildlife habitats and degradation of watershed area, considering with these negative impacts a revegetation programme is fully needed (Setiadi 1995). Revegetation that has been done obstacled by the marginal land conditions where soil structure has been damaged and it has became a lateritic soil. It absorbs elements of phosphate (P), which is essential for plant life. It will be poor of P-available that can be absorbed by plants. Therefore input for more effective technology and environmentally friendly is needed, among others by applying a bio-technology Arbuscular Mycorrhizal Fungi biofertilizer (AMF). It has some functions, one of them is increasing nutrients absorption, especially P. Therefore, research on the existence of mycorrhizal status needs to be done as an introduction for research and application of mycorrhizal in the rehabilitation field of post- nickel mining.